Numerical Simulations of Fiber Sedimentation in Navier-Stokes Flows (Communications in Computational Physics, 2018)
We perform numerical simulations of the sedimentation of rigid fibers suspended in a viscous incompressible fluid at nonzero Reynolds numbers. The fibersedimentation system is modeled as a two-dimensional immersed boundary problem, which naturally accommodates the fluid-particle interactions and which allowsthe simulation of a large number of suspending fibers. We study the dynamics ofsedimenting fibers under a variety of conditions, including differing fiber densities,Reynolds numbers, domain boundary conditions, etc. Simulation results are comparedto experimental measurements and numerical results obtained in previous studies.